PERBEDAAN PERSEPSI MAHASISWA PROGRAM STUDI AKUNTANSI DAN MANAJEMEN TERHADAP KUALITAS LAYANAN JASA PENDIDIKAN DI UNIVERSITAS KATOLIK MUSI CHARITAS PALEMBANG - Maria Josephine Tyra; Andreas Sarjono (Jurnal Keuangan dan Bisnis, 2018)
The research is aim to observe consumer behavior regarding the perception of the five dimensions of education quality including reliability, responsiveness, assurance, empathy, and physical evidence from the Musi Charitas Catholic University (MCCU). The purpose of the study is to prove whether there is a difference in the perception of education qualityfrom the students in Management and Accounting Study Program. Data collection techniques used is to spread the 5-point Likert questionnaire that is from very disagree until strongly agree.Population in this research is active student, Batch 2015/2016 untilBatch 2016/2017 Management and Accounting Study Program. Based on the results of the differences test using the Mann-Whitney test proved that the perception of Accounting studentson the quality of education (Mdn = 2143) generaly difference and significant with the students perception of Managementon the quality of education in MCCU (Mdn = 2907) with significance 0.008 <0.05 (Ho is rejected). If it is seen from each variable, then reliability, responsiveness, and guaranteeprove the difference of perception between student of Accounting and Management Study Program. While the variable of empathy and physical evidence didn’t prove the difference of perception between student of Accounting and Management Study Program.